Phenotypic Diversity and Socio-Economic Data Related to Village Pig Farming in Kalamulla, Kalutara District of Sri Lanka - Mallikarachchi, M.M.; Wijayawardhana, D.; Somasiri, S.C. (University of Jaffna, 2025)
Village pigs (VP) are the native pigs in Sri Lanka. However, data on population diversity is scarce. A study was undertaken to investigate the phenotypic diversity of VP and socio economic status related to VP farming. Phenotypic data were collected from a population of 26 VP (n=3 sows, n=7 boars, n=3 sucklings, n=4 barrows and n=9 gilts) in Kalamulla, Kaluthara district. Qualitative data included coat colour type and pattern, ear type and orientation, tail type, and snout shape, while quantitative data included body weight, body length, tail length, ear length, chest girth, height at withers, abdominal circumference, and face length. A pre-tested structured questionnaire was used to collect socio-economic data from seven VP-rearing farmers. All the data were analyzed using R statistical software. Black colour was the dominant coat colour (50%) of the population. White-black (34.7%), black-white (11.5%) and white (3.8) coat colour were also prominent. The population had only smooth skin type, straight head profile and straight hair type. Most of the VP had a forward-oriented, erect ear type (77%) and straight backline. The majority of VP had long and thin snouts (61.5%) and curly tails (54.0%). Only 3.8% of VP had tusks. Body weight, body length, tail length, ear length, chest girth, height at withers, abdominal circumference, and face length were 25.7±4.29, 64.1±3.75, 21.0±1.49, 10.2±0.53, 67.1±4.31, 45.3±2.16, 73.0± 4.86 and 21.2±1.06 cm, respectively. The VP were reared under a free-range backyard system for meat purposes. They are fed with swill obtained from the nearby hotels in Kaluthara. The majority (71.5%) of farmers had medium-sized (10-50 animals) herds. Village pigs receive little veterinary care or government attention. Despite being raised in harsh conditions, they offer high returns due to low maintenance costs. However, their population is declining, and without prompt action from stakeholders, these pigs may soon face extinction in the region.
Keywords: Free range system; Native pigs; Population diversity; Qualitative and quantitative data